Pengaruh pembelajaran Pendidikan Pancasila berbantuan media interaktif Quizizz terhadap hasil belajar siswa - Sartika Rafinka; Zaky Farid Luthfi; Isnarmi Moeis; Junaidi Indrawadi (Journal of Education, Cultural and Politics, 2026)
Abstract written italic in Verdana 11 pt. Abstract is written with a length of 150-200 words. This abstract should provide a brief introduction to the problem, the purpose of the paper, followed by a statement about the methodology and a brief summary of the results. This study is motivated by the low student learning outcomes in Pancasila Education caused by the use of conventional teaching methods and the lack of technology-based learning media. This research aims to determine the effect of using Quizizz interactive quiz media on students’ learning outcomes in the topic of the Unitary State of the Republic of Indonesia (NKRI). This study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample consisted of two classes, namely the experimental class and the control class, each consisting of 31 students. Data were collected through tests (pretest and posttest) and student response questionnaires. Data analysis included normality tests, homogeneity tests, and hypothesis testing using the Independent Samples T-Test. The results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant effect of Quizizz on student learning outcomes. The average posttest score of the experimental class (86.71) was higher than that of the control class (70.97). Thus, Quizizz is effective in improving student learning outcomes.